SOME PROBLEMS IN GOVERNMENT ACCOUNTING. - Green, Paul M. (The Accounting Review, 1936)
The National Housing Act provides for the insurance of mortgages. Section 205 of the act states that all mortgages accepted for insurance shall be so classified into groups and that the mortgages in any group shall involve substantially similar risk characteristics and have similar maturity dates. Premium charges received for the insurance of the mortgage and earnings from all properties taken over by the administrator shall be credited to the group account. However, there are several accounting problems raised by the act. There is room for considerable variation in the interpretation of the law that will have a bearing upon the accounting procedure to be established. There is little question that the accountant is required to classify the mortgages into groups of similar risk characteristics and similar maturity dates. When the groups have been established, they may be liquidated in two ways. First, when the balance in the group account exceeds the outstanding balance of the mortgages in the group by ten per cent of the total premiums paid and, second, when the balance in the account fails to reach the above figure one year before maturity of the mortgages, ten per cent of the premiums paid shall be transferred to the general reinsurance account and the balance, if any, transferred to the mortgages for the benefit of the mortgagors.